Effects of browse supplementation on the productivity of West African dwarf goats - Reynolds, L. (International Livestock Centre for Africa, 1989)
A trial involving 28 West African Dwarf (WAD) goats fed 4 levels of supplement of Leucaena leucocephala and Gliricidia sepium over a basal diet of Panicum maximum and dried cassava peels was conducted over 2 reproductive cycles. The provision of supplementary browse to pregnant and lactating goats and to their offspring from weaning to 24 wk improved growth and survival rates of the offspring. Productivity, calculated as weight of kid weaned/doe/yr increased by 0.64 kg for each 100 g of browse DM consumed by the does daily. Intake of DM increased as the level of supplementation rose, reaching 180 g/kg0 75/d for lactating adults. Growth rates of kids and productivity of dams was about half that recorded in earlier trials with WAD sheep which had a similar food intake.